Strategic Information Systems Planning (SISP) Practices in Health Care Sectors of Rwanda - Emmanuel, Gahizi none (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
Strategic Information Systems Planning (SISP) is an area of great value in information technology as concerns and interests to Information Systems. SISP has consistently been ranked the top issue for IS executive since 1970â€™s in developed and non-developed countries.Studies show that Strategic Information Systems Planning (SISP)can help the manager to design information systems, develop IS strategy and distribute resources for IS strategy. However, in Rwanda ,the use of SISP in healthcare sectors Â is still limited and under-researched. The key goal of this research is to find out the positive impactÂ and the gain for putting into practice the SISP to Developing countries, particularly Rwanda Health sector. The research is aimed at provingthe limitations of the existing Information Systems within the healthcare sector of Rwanda.Furthermore, Hybrid SWOT approach will be used to give solutions to the challenges faced in the implementation of SSIP for health sectors in Rwanda.